Childbirth Yesterday and Today: A Comparative Analysis of Women’s Experiences and Feelings through the Ages to the Present - Bączek, Grażyna; Jasińska, Joanna (Archives of Business Research, 2020)
Introduction: Perinatal care has undergone many changes over time. Therefore, women’s feelings and experiences will differ depending on the perinatal care provided at the time of childbirth. Time of childbirth and the perinatal care received are the main determinants in this process. However, one thing remains unchanged over time. Childbirth is considered one of the most notable events in the life of every woman. The aim of the study was a comparative analysis of experiences and feelings shared by females giving birth in the past and the present in Poland. Material and methods: A questionnaire was designed specifically for this research project. It was a set of multiple choice (single answer) questions concerning childbirth conditions and perinatal care. Results were analyzed with a chi square test. Data was collected in 2016 in Poland. The questionnaire was distributed both in paper and electronic form. Results: The study group comprised of 671 females divided into three groups: childbirth before 2000, between 2001–2012, and after 2013. This time frame was associated with significant changes in perinatal care in Poland over the years. Changes in the delivery rooms have raised the comfort of childbirth, but progression of obstetrics resulted in greater medicalization of childbirth.